La disarmonia originaria: epopea, tragedia e commedia (ENTHYMEMA, 2013)
Evoking Hegel’s identification of three figures in literature, outlined in his Phenomenology of the Spirit, the essay connects the interpretation of the subject that surfaces in the philosophy of Ricœur with a form of triple disharmony. The tragic subject is that torn by moral issues, the comic subject – free-spirited and careless, connects with practical knowledge, and the epic subject identifies with the ‘us’ but, at the same time, in conformity with Kant’s understanding of the limit, conceives the Hegelian totality as desire or aspiration.